Controlling the morphology and crystallization of a thiophene-based all-conjugated diblock copolymer by solvent blending. Issue 31 (12th July 2017) - Cui, Huina; Yang, Xiubao; Peng, Juan; Qiu, Feng
Abstract : We report the crystallization and microphase separation behavior of an all-conjugated poly(3-hexylthiophene)- b -poly[3-(6-hydroxy)hexylthiophene] (P3HT- b -P3HHT) block copolymer in mixed solvents and demonstrate how the conformations of P3HT and P3HHT chains influence the photophysical properties of the copolymer. Abstract : We report the crystallization and microphase separation behavior of an all-conjugated poly(3-hexylthiophene)- b -poly[3-(6-hydroxy)hexylthiophene] (P3HT- b -P3HHT) block copolymer in mixed solvents and demonstrate how the conformations of P3HT and P3HHT chains influence the photophysical properties of the copolymer. It is shown that the balance among π–π stacking of P3HT, P3HHT and microphase separation of the copolymer can be dynamically shifted by controlling the rod–rod interactions of the copolymer via changing the block ratio and solvent blending. A series of nanostructures such as well-ordered nanofibers, spheres and lamellar structures are formed and their formation mechanisms and kinetics are discussed in detail. The variations in P3HT- b -P3HHT conformations are concomitant with a hybrid photophysical property depending on the competition between intrachain and interchain excitonic coupling, resulting in the transformation between J- and H-aggregation. Overall, this work demonstrates how the P3HT- b -P3HHT conformations crystallize and phase-separate in the solution and solid state, and the correlation between their structures and photophysical properties, which improves our understanding of all-conjugated rod–rod block copolymer systems.